The Philosophical Origins of Professional Self-Improvement of Primary School Teachers - Shestakova, Tetiana (Pedagogical Discourse, 2019)
Based on a deep analysis of the development of the idea of self-improvement in the history of philosophical thought, the article highlights and describes an idealistic, materialistic and dialectical understanding of self-improvement of a person, presents their comparative characteristics and emphasizes their importance for the formation of a personal worldview position regarding professional self-improvement among primary school teachers. Idealistic understanding is based on the recognition of the self-improvement of the self as a purely internal activity aimed at the development of spirituality, enriching the inner world of man by actualizing the potential strengths and capabilities. The materialistic approach characterizes self-improvement as the predominantly external activity of a person aimed at achieving the socially determined and socially conditioned ideal of mental, physical and moral perfection by correcting one’s own activity and behavior in accordance with the norms and values of a certain society for self-assertion in it. In a dialectical approach, idealistic and materialistic views on the nature of this phenomenon are harmonized on the basis of the unity of opposites and the primacy of humanistic values, whereby self-improvement of the individual is interpreted as activity aimed at both the enrichment of the inner world and the perfection of the outside world. The author made an attempt to classify primary school teachers according to the dominant tendencies of their personal professional self-improvement into idealistic teachers, pragmatists, and harmonizers. The importance of familiarizing future primary school teachers with the above philosophical approaches in understanding the essence and content of self-improvement of the person is emphasized.